2004
DOI: 10.1126/science.1092316
|View full text |Cite
|
Sign up to set email alerts
|

CD8αα-Mediated Survival and Differentiation of CD8 Memory T Cell Precursors

Abstract: Memory T cells are long-lived antigen-experienced T cells that are generally accepted to be direct descendants of proliferating primary effector cells. However, the factors that permit selective survival of these T cells are not well established. We show that homodimeric alpha chains of the CD8 molecule (CD8alphaalpha) are transiently induced on a selected subset of CD8alphabeta+ T cells upon antigenic stimulation. These CD8alphaalpha molecules promote the survival and differentiation of activated lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
3
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(219 citation statements)
references
References 25 publications
13
201
3
1
Order By: Relevance
“…Furthermore, IL-7R + or CD8αα + effector cells preferentially survive the contraction phase and differentiate into memory cells. In CD8αα deficient mice, CD8 + memory T cell formation after acute infection is compromised [206]. These data suggest that CD8αα delivers a pro-survival signal to CD8 + memory T cell precursors.…”
Section: Memory Phase Of Cd8 + T Cell Immune Re-sponsementioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, IL-7R + or CD8αα + effector cells preferentially survive the contraction phase and differentiate into memory cells. In CD8αα deficient mice, CD8 + memory T cell formation after acute infection is compromised [206]. These data suggest that CD8αα delivers a pro-survival signal to CD8 + memory T cell precursors.…”
Section: Memory Phase Of Cd8 + T Cell Immune Re-sponsementioning
confidence: 80%
“…Alternatively, apoptosis during the contraction phase may be a completely random event. Recently, IL-7R and CD8αα have been identified as markers to identify the early precursors of memory cells within the effector cell population [205,206]. IL-7R + or CD8αα + effector T cells have higher expression levels of anti-apoptotic Bcl-2 family members when compared with their IL-7R -or CD8αα -counterparts.…”
Section: Memory Phase Of Cd8 + T Cell Immune Re-sponsementioning
confidence: 99%
“…Although studies using LCMV-infected mice have shown that these two molecules can mark CD8 + memory cell precursors [26][27][28]31], other studies using peptide-pulsed DCs or peptide immunization have shown that IL-7R is not a marker for such precursors [38][39][40][41]. Antigen-presenting cells expressing thymic leukemia antigen TL can boost CD8αα expression by T cells, and CD8αα expression induces IL-7Rα expression [29]. Our work showed elevated expression of TL on LV-SOCS1-siRNADCs compared to control DCs, so we would expect to see increased expression of IL-7R and CD8αα.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of the two molecules triggers signaling that results in a CD8 + T cell becoming a memory T cell [29]. We analyzed levels of TL on DCs using an anti-TL antibody and flow cytometry, and we found that LV-SOCS1-siRNA-DCs, upon stimulation with LPS, increased expression of surface TL significantly more than control DCs (Fig.…”
Section: Lv-socs1-sirna-dcs Expressed Higher Levels Of Surface Tl Thamentioning
confidence: 91%
See 1 more Smart Citation